Republic of Belarus : Technical Assistance Report-Asset Classification and Nonperforming Loan Regulation. (IMF Staff Country Reports; Country Report ;, 2021)
The NBRB revised in 2018 its regulation on asset classification and provisioning (the Regulation). One of the main changes was the introduction of a new definition for NPLs based on the current framework of risk groups (RGs). This definition substitutes the previous term "problem assets." One of the intentions of the replacement is to promote international comparability by using it as a financial soundness indicator (FSI). The reported levels of this new NPLs indicator are, however, relatively low and, more important, much lower than the previous indicator, based on problem assets. The new NPL indicator levels are relatively stable, around 4 percent. The previous indicator was also stable, but the levels were more than three times higher, about 13 percent.